Study of the effect of annealing during and after deposition on (crystal growth and some physical properties) of zinc sulfide (ZnS) nanoparticles prepared by vacuum thermal evaporation method (PVD) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
research deals with the study of the effect of annealing during and afterdeposition on the optical and structural properties for zinc sulfide (ZnS) filmsprepared on Soda glass bases under pressure (10^(-5) torr) by vacuum thermalevaporation method. Then studying the crystal growth of thin films through the resultshave been obtained, where the optical properties were studied during deposition bytaking temperatures ((50°C, 100°C, 150°C, 200°C) for an hour and after depositingannealing at temperatures (R.T, 250°C, 300°C, 350°C) using a spectrometer fromType (UV-Visible). It has been found during deposition that the transmittanceincreases oscillating correspondingly with the increase in the wavelength of thephoton while it increases more oscillatory so that the transmittance eV (68,75,82,88)corresponding to the temperature (R .T,250°C, 300°C,350°C ). The energy gapdecreased from eV (3.7,3.65,3.63,3.6) corresponding to temperatures(200°C,150°C,100°C,50°C) to eV (3.44,3.45,3.47,3.48) corresponding totemperatures Temperature (350°C, 300°C, 250°C, R.T after annealing.